Role of Intravenous Ketamine as Adjuvant to Opioids in Refractory Cancer Pain: Case Report - Regmi, Yogesh; Sapkota, Ganga; Wagle, Bhawna (Nepalese Journal of Cancer, 2019)
Cancer pain is caused by continuous tissue injury, which may be due to surgery, infiltration of the surrounding organs including nerves, as well as from mucositis after chemo- or radiotherapy. The pain experienced by cancer patients needs a multimodal approach, including ketamine. Nerve involvement, chronic opioid therapy and continuous nociceptive input cause hyperalgesia. Chronic stimulation of the dorsal root neurons leads to hyperalgesia and resistance (tolerance) to μ opioid analgesics (hyperalgesia-tolerance). The NMDA receptor antagonist ketamine reverses tolerance to morphine. The management of cancer patient’s pain with ketamine as an adjuvant to opioids is presented in case reports of two patients with cancer-related neuropathic pain, in which pain proved untreatable with the usual conventional pain therapies. Ketamine was administered IV route, in addition to morphine and the pain was controlled successfully in these patients. No side-effects were noted except drowsiness which responded to a reduction in the opioids dose.